Study on influencing factors and mechanism of pore compressibility of tight sandstone reservoir—A case study of upper carboniferous in ordos basin - Hu, Yunbing; Guo, Yinghai; Qing, Hairuo; Hou, Yundong (Frontiers in Earth Science, 2023)
A series of studies were carried out on 11 tight sandstone samples of Upper Carboniferous in Ordos Basin. Firstly, the deposit composition and pore structure characteristics are investigated based on analysis and experiments including cast thin section scanning electron microscope high-pressure mercury intrusion and nuclear magnetic resonance Then, combined with DP-P test, the stress-dependent permeability change and pore compressibility characteristics of sandstone reservoirs were studied to reveal the influencing factors and mechanism of reservoir pore compressibility. The detrital particles of the sandstone reservoir in the study area are mainly quartz (75.8%–89%), followed by fragments (3%–16.1%), and almost no feldspar. The content of interstitial materials is 6.5%–11.2%. The type I reservoirs mainly consist of mesopores and macropores, accounting for 60.57% and 32.84% respectively. Mesopores are dominated in Type II reservoirs, accounting for 78.98% of the total pore volume. There are almost no macropores, while a similar proportion of mesopores, micro mesopores and micropores in the type Ⅲ reservoirs. The study of pore compressibility shows that the pore compressibility coefficient decreases with the increase of effective stress, and the reduction rate shows the two-stage characteristics of rapid in the early stage and slow in the later stage. The pressure turning point is between 3 and 10 MPa. The average pore compressibility coefficient increases from type I to type Ⅲ reservoirs. The compressibility coefficient is directly proportional to the changing rate of the pore volume. The higher the content of rigid detrital particles, quartz and carbonate cement in sandstone, the smaller the pore compressibility coefficient, while the higher the content of ductile components such as soft rock fragments and clay minerals, the greater the pore compression coefficient. The pore-throat structure is closely related to the pore compressibility, reservoirs with low displacement pressure, T2glm value, and large average pore-throat radius show lower compressibility coefficient. In addition, the compressibility coefficient of the reservoir is positively correlated with DL (dimension of large pores such as mesopores and macropores), and negatively correlated with DS (the fractal dimension of micropores and micro mesopores). It is considered the pore compression of sandstone including two stages, viscoplastic destructive deformation of ductile components for the first and then the small-scale non-ideal elastic deformation on rigid particles.